Inspecting the Occurrence of Fungi In Rhizospheric Soil From Irrigated And Non-Irrigated Maize Crop Fields In Sillod Taluka - Salve S. S.,; Badar K. V.,; Magar S. D., (International Journal of Scientific Research in Science and Technology, 2024)
Soil is the chief medium for the growth of the crops as well as the absorption of nutrients by roots and hence, only good quality soil has the ability to grow good quality crops. In the soil-plant interaction, the soil microbial communities are actively participating in the biomass and energy flow of the ecosystem and is considered as the most active component of soil ecosystem affected by a range of factors, such as irrigation systems, planting patterns, soil type and climatic changes. Irrigation is one of the most important factor of them. The rhizosphere of a plant root occupies a portion of soil that extends from the root to a non-defined extent in the soil that normally depends upon the diffusion of root secretions and the stage of development of the roots under the soil. Rhizosphere has very extreme amount of readily degradable carbon compounds and other nutrients made available by the rhizodepositions.
Keywords: Nutrients; Interaction; Rhizosphere; Irrigation; Rhizodeposition; Microbial Activity; Microorganisms